2012
DOI: 10.1117/1.jbo.17.7.071306
|View full text |Cite
|
Sign up to set email alerts
|

Imaging a photodynamic therapy photosensitizerin vivowith a time-gated fluorescence tomography system

Abstract: Abstract. We report the tomographic imaging of a photodynamic therapy (PDT) photosensitizer, 2-(1-hexyloxyethyl)-2-devinyl pyropheophorbide-a (HPPH) in vivo with time-domain fluorescence diffuse optical tomography (TD-FDOT). Simultaneous reconstruction of fluorescence yield and lifetime of HPPH was performed before and after PDT. The methodology was validated in phantom experiments, and depth-resolved in vivo imaging was achieved through simultaneous three-dimensional (3-D) mappings of fluorescence yield and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
22
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 79 publications
2
22
0
Order By: Relevance
“…TRF studies relevant to different PDT photosensitizers have been reported by several research groups in the past decades [31,43,45,[70][71][72][73][74][75][76]. FDA-approved PDT photosensitizers include Photofrin ® , 5-aminolevulinic acid-induced protoporphyrin IX (ALA-PpIX), and verteporphyrin, Other photosensitizing agents in research stage, such as mTHPC (m-tetrahydroxyphenylchlorin, Foscan ® ), phthalocyanine (Pc) compounds, and chlorin-based compounds (i.e., HPPH), also showed promising results in terms of their singlet oxygen yield and more red-shifted absorption bands [77].…”
Section: Time-resolved Studies Of Pdt Photosensitizers In Solution Anmentioning
confidence: 99%
See 4 more Smart Citations
“…TRF studies relevant to different PDT photosensitizers have been reported by several research groups in the past decades [31,43,45,[70][71][72][73][74][75][76]. FDA-approved PDT photosensitizers include Photofrin ® , 5-aminolevulinic acid-induced protoporphyrin IX (ALA-PpIX), and verteporphyrin, Other photosensitizing agents in research stage, such as mTHPC (m-tetrahydroxyphenylchlorin, Foscan ® ), phthalocyanine (Pc) compounds, and chlorin-based compounds (i.e., HPPH), also showed promising results in terms of their singlet oxygen yield and more red-shifted absorption bands [77].…”
Section: Time-resolved Studies Of Pdt Photosensitizers In Solution Anmentioning
confidence: 99%
“…How these factors affect lifetime measurements of the photosensitizers will be further discussed. [43] 10 ns (Organic solution) [70] 5.5 ns (Mitochondria, MLL) [70] 13.3 ns (Monomer, mitochondria) [70] 13.6 ns (Monomer, mitochondria) [45] 8.5 ns (Aggregates, mitochondria) [45] 8.0 ns (Aggregates, mitochondria) [78] 4.8 ns (Cell membrane) [78] 1.0 ns (Aggregates, mouse model) [31] 13 ns (Monomers, mouse model) [31] 5 µg/mL 0.06-6 µg/mL 7.6 ns (liposome confined) [74] 6.4 ns (tissue phantom) [75] 4.3 ns (mouse tumor, before PDT) [75] 5.0 ns (mouse tumor, after PDT) [75] …”
Section: Time-resolved Studies Of Pdt Photosensitizers In Solution Anmentioning
confidence: 99%
See 3 more Smart Citations